2007
DOI: 10.1016/j.febslet.2007.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the formation of start aggregates as an initial stage of protein aggregation

Abstract: The kinetics of thermal aggregation of glycogen phosphorylase b and glyceraldehyde 3-phosphate dehydrogenase from rabbit skeletal muscles were studied using dynamic light scattering. Use of high concentrations of the enzymes (1-3 mg/ml) provided a simultaneous registration of the native enzyme forms and protein aggregates. It was shown that initially registered aggregates (start aggregates) were large-sized particles. The hydrodynamic radius of the start aggregates was about 100 nm. The intermediate states bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…241 Increasing the concentration of cold shock protein A reduced the lag time (to the power of 2.1 of the protein concentration). 248 Increasing the concentration of glycogen phosphorylase b from 1 to 3 mg/mL not only shortened the lag time but also increased the aggregation rate at pH 6.8 at 37 ° C. 249 Increasing the concentration of rhIL -1ra shifts the rhIL -1ra monomer -dimer equilibrium signifi cantly to favor dimerization at low ionic strength at 37 ° C. 35 The aggregation dependency on protein concentration may vary depending on the experimental conditions. The fi rst -order rate constant for the aggregation of creatine kinase at pH 8.0 was found to increase with increasing protein concentration in the range 0.1 -0.4 mg/mL at 60 ° C but was found to be protein concentration independent in the range 0.05 -0.2 mg/mL at 50.6 ° C. 134 The aggregation kinetics may or may not follow second order, even though high protein concentrations accelerate protein aggregation.…”
Section: Enhanced Protein Aggregation At High Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…241 Increasing the concentration of cold shock protein A reduced the lag time (to the power of 2.1 of the protein concentration). 248 Increasing the concentration of glycogen phosphorylase b from 1 to 3 mg/mL not only shortened the lag time but also increased the aggregation rate at pH 6.8 at 37 ° C. 249 Increasing the concentration of rhIL -1ra shifts the rhIL -1ra monomer -dimer equilibrium signifi cantly to favor dimerization at low ionic strength at 37 ° C. 35 The aggregation dependency on protein concentration may vary depending on the experimental conditions. The fi rst -order rate constant for the aggregation of creatine kinase at pH 8.0 was found to increase with increasing protein concentration in the range 0.1 -0.4 mg/mL at 60 ° C but was found to be protein concentration independent in the range 0.05 -0.2 mg/mL at 50.6 ° C. 134 The aggregation kinetics may or may not follow second order, even though high protein concentrations accelerate protein aggregation.…”
Section: Enhanced Protein Aggregation At High Concentrationsmentioning
confidence: 99%
“…If such an effect dominates protein -protein association, aggregation may be reduced at higher concentrations. Increasing the concentration of glyceraldehyde 3 -phosphate dehydrogenase from 1 to 3 mg/mL not only prolonged lag time but also reduced the aggregation rate at pH 7.5 at 45 ° C. 249 Increasing the concentration of PEG -GCSF from 1 to 10 mg/ mL gradually inhibited the agitation -induced aggregation at 23 ° C. 232 If the aggregation tendency of monomers is higher than that of polymers, reduced aggregation could also be seen at higher concentrations due to polymer formation. The aggregation tendency of human IFN -γ dimer was found to be less competent in aggregation than the monomer, and increasing human IFN -γ concentration from 1 to 4 µ M delayed the time of reaching maximum aggregation.…”
Section: Unaltered or Reduced Protein Aggregation At High Concentrationsmentioning
confidence: 99%
“…When studying the kinetics of thermal aggregation of proteins using dynamic light-scattering (DLS), it was demonstrated that the initial stage of the aggregation process was formation of the start aggregates [1,2]. Each start aggregate contains hundreds of denatured protein molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic radius of the start aggregates was tens of nanometers. The start aggregate formation was revealed in the process of thermal aggregation of the following model substrates: β L -crystallin from bovine lens [1], glyceraldehyde-3-phosphate dehydrogenase and glycogen phosphorylase b from rabbit skeletal muscle [2][3][4][5][6], aspartate aminotransferase from pig heart mitochondria [7] and tobacco mosaic virus coat protein [8].…”
Section: Introductionmentioning
confidence: 99%
“…The protein particle size was observed to evaluate thermal stability of PHA synthase (Golub et al 2007). Four hundred micro liter of PHA synthase (0.5mg•mL -1 ) dissolved in 100 mM sodium phosphate buffer (pH 7.5) was put into a sample cell kept at 37 °C.…”
Section: Thermal Stability Testmentioning
confidence: 99%